Enzymatic and non-enzymatic isolation systems for adipose tissue-derived cells: current state of the art. Issue 1 (December 2015) - Oberbauer, Eleni; Steffenhagen, Carolin; Wurzer, Christoph; Gabriel, Christian; Redl, Heinz; Wolbank, Susanne
Abstract In the past decade, adipose tissue became a highly interesting source of adult stem cells for plastic surgery and regenerative medicine. The isolated stromal vascular fraction (SVF) is a heterogeneous cell population including the adipose-derived stromal/stem cells (ASC), which showed regenerative potential in several clinical studies and trials. SVF should be provided in a safe and reproducible manner in accordance with current good manufacturing practices (cGMP). To ensure highest possible safety for patients, a precisely defined procedure with a high-quality control is required. Hence, an increasing number of adipose tissue-derived cell isolation systems have been developed. These systems aim for a closed, sterile, and safe isolation process limiting donor variations, risk for contaminations, and unpredictability of the cell material. To isolate SVF from adipose tissue, enzymes such as collagenase are used. Alternatively, in order to avoid enzymes, isolation systems using physical forces are available. Here, we provide an overview of known existing enzymatic and non-enzymatic adipose tissue-derived cell isolation systems, which are patented, published, or already on the market.